A Review of Emotions in Second Language Acquisition from a Positive Psychology Perspective - Wang, Yujie (International Journal of Education and Humanities, 2024)
Since the 21st century, many scholars have adopted the perspective of positive psychology (PP) to study emotions in second language acquisition (SLA). This study aims to interpret the connotation and development of PP, introduce the three stages of SLA study from the PP perspective, and discuss the study on emotions in SLA from theoretical foundations, study topics, and study methods. Through the analysis of relevant literature from both domestic and international sources, this study finds that: 1) Theories related to PP are continually deepening and innovating; 2) Study topics in this field are diverse, with further potential for study in online learning environments; 3) Study methods are varied, yet there remains significant room for innovation in study design, scenarios, participants, and tools. The study provides implications for foreign language education in China, suggesting that future study should explore the impact of PP in online learning environments and develop more innovative and diverse study tools